ANALYSIS OF DA’WAH MESSAGES THROUGH CONTENT ON TIKTOK ACCOUNT @ZAHIDSAMOSIR - Mafidah, Cindy; Mutrofin, Mutrofin (UIN Kiai Ageng Muhammad Besari Ponorogo, 2023)
This research reviewed the analysis of da'wah messages on content on a Tiktok account. Where in this modern phenomenon the practice of preaching can be done anywhere, including on social media platforms. In this era of modernization, the existence of da'wah practices must be increasingly improved. The enforcement of religious teachings must still exist and be broadcast. However, in order to get attention and be able to attract mad'u to be able to listen to da'wah, various strategies must be used to keep up with the times. Digital da'wah through social media has become the most effective strategy for seeking mad'u from various circles. One of the most popular social media is TikTok. It is a social media platform that can share videos, making many da’is use it as a medium for preaching. Zahid Samosir with the account name TikTok @zahidsamosir utilizes the TikTok platform as a media for da'wah creativity that is packaged through content so that Zahid now has many followers and fans and has a large number of views on each of his content. Through his TikTok platform, Zahid broadcasts da'wah messages through short video content in a millennial and easy-to-understand language style.